Organization development in healthcare conversations on research and strategies - Wolf, Jason A. (Advances in health care management ;, 2011)
This volume is a collection of critical ideas relating organization science to both operations and accomplishments in the health care environment. A thematic guide for current leaders and practitioners, as well as health administration, business administration and organization development professors and students alike, this work pulls in a broad cross-section of perspectives on the important linkage of scholarship and practice with a solid global perspective. Covering key themes from culture, change, leadership, teams, IT and a systemic perspective of health care overall, it provides both practical insights and theoretical perspectives that will support immediate improvements and encourage longer term dialogue on how organization science can impact the delivery, structure and operations of health care systems globally. Advances in Health Care Management provides a forum for leading research on health care management with previous volumes providing reviews of the field, conference papers and research on selected topics including bioterrorism, international health care management, entrepreneurship, patient safety and nursing and health professional shortages.